Semi-local duality and FESR problems for Venezian models - de Atcherberg, M. C.; Della Selva, A.; Masperi, Luis; Page, R. (Societa italiana di fisica, 1973)
Fil: de Atcherberg, M. C. Universidad de Buenos Aires; Argentina